Male and female interactions during courtship of the Neotropical damselfly Mnesarete pudica (Odonata: Calopterygidae) - Guillermo-Ferreira, Rhainer [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Springer Heidelberg, 2012)
The courtship behavior in calopterygid damselflies is well documented; however, the behavior of the large Neotropical genus Mnesarete is still unknown. Thus, here we present the first description of male-female interactions in Mnesarete pudica, a common damselfly in the Neotropical Savanna. The male-female interactions were composed of courtship displays, mounting, and chasing. The courtship behavior lasted 5.23 +/- 1.65 s and is very different from other calopterygids, consisting of hovering flights and the cross display made in front of females rather than on the oviposition site. The arrival and presence of females on a male territory are not sufficient to initiate sexual interactions; the male usually interacts with the female only after a patrolling flight. The females may present three distinct behaviors in response to male approach: (a) warding off signal (31.53%), (b) escape (28.83%), (c) and wing flipping (39.64%), which seems to stimulate male courtship. Females also may sit still, which induces males to react as if females were signaling they are willing to mate. In this paper, we also suggest that male courtship behavior is mediated by female signals.
Keywords: Reproductive behavior; Mnesarete; Calopterygidae; Odonata; Mate choice